Peripheral myopization using a dominant design multifocal contact lens - Lopes, Daniela (2011)
Purpose: The purpose of this study was to characterize the central and peripheral refraction across the horizontal meridian of the visual fi eld without and with a multifocal dominant design soft contact lens of different add powers (+1.00 D to +4.00 D) in emmetropic eyes. Methods: Twenty right eyes from 20 emmetropic patients (mean spherical equivalent central refraction —0.06 ± 0.54 D) with a mean age of 21.6 ± 2.3 years were fi tted with Proclear Multifocal dominant design (Coopervision, Pleasanton, CA, USA). Lenses had add powers from +1.00 to +4.00 D in 1.00 D steps. The central and peripheral refraction was measured along the horizontal meridian up to 35º of eccentricity in the nasal and temporal retinal area in 5º steps using a open-fi eld autorefractometer. Results: Only the +3.00 and +4.00 D add powers generated a signifi cant change in the peripheral refractive pattern compared to central refraction and compared with the no-lens wearing situation. The average myopic increase with these lenses was —3.00 D and —5.00 (p < 0.001) at the margins of inspected nasal and temporal visual fi eld, respectively. Conclusions: Multifocal dominant design soft contact lenses are able to change the peripheral refractive profi le in emmetropic eyes increasing relative peripheral myopia. Lenses with +3.00 D add power seem to be the best option to create such effect due to signifi cant peripheral myopization.